Effects of long‐term phosphorus fertilizer inputs and seasonal conditions on organic soil phosphorus cycling under grazed pasture. (24th July 2022) - Touhami, Driss; Condron, Leo M.; McDowell, Richard W.; Moss, Ray
Abstract: Soil microbes and phosphatase enzymes play a critical role in organic soil phosphorus (P) cycling. However, how long‐term P inputs influence microbial P transformations and phosphatase enzyme activity under grazed pastures remains unclear. We collected top‐soil (0–75 mm) from a grazed pasture receiving contrasting P inputs (control, 188 kg ha −1  year −1 of single super phosphate [SSP], and 376 kg ha −1  year −1 of SSP) for more than 65 years. Olsen P, microbial biomass P, and acid and alkaline phosphatase enzyme activities were measured regularly over a 2‐year period. Pasture dry matter and soil chemical properties were also investigated. Results showed that long‐term P inputs significantly increased pasture dry matter, total N, and the concentrations of NO 3 – –N but significantly decreased soil pH and the concentrations of NH 4 + –N. Total C was not affected by P fertilization. Although Olsen P significantly increased with increasing long‐term P inputs, microbial biomass P was similar under P fertilized treatments. Long‐term P inputs decreased acid phosphatase activity but increased alkaline phosphatase activity. Microbial biomass P was similar across seasons in the control but decreased in spring and autumn while increased in summer and winter under P fertilized treatments. Acid and alkaline phosphatase activities were significantly affected by season and followed similar seasonal trends being maximum in summer and minimum in winter regardless of P treatment. Correlation and principal component analysis revealed that acid and alkaline phosphatase activities were significantly positively correlated with soil temperature and significantly negatively correlated with soil moisture. In contrast, Olsen P and microbial biomass P were weakly correlated with environmental conditions. The findings of this study highlight the intertwined relationship between organic P cycling and the availability of C and N in soil systems and the need to integrate both soil moisture and temperature in models predicting organic P mineralization, especially in the context of global climate change.